External validation of the PROGRESS‐CTO perforation risk score: Individual patient data pooled analysis of three registries. Issue 2 (8th January 2023) - Simsek, Bahadir; Tajti, Peter; Carlino, Mauro; Ojeda, Soledad; Pan, Manuel; Rinfret, Stephane; Vemmou, Evangelia; Kostantinis, Spyridon; Nikolakopoulos, Ilias; Karacsonyi, Judit; Rempakos, Athanasios; Dens, Joseph A.; et al.
Abstract: Background: Coronary artery perforation is one of the most feared and common complications of chronic total occlusion (CTO) percutaneous coronary intervention (PCI). Methods: To assess the usefulness of the recently developed PROGRESS‐CTO (NCT02061436) perforation risk score in independent cohorts. Individual patient‐level data pooled analysis of three registries was performed. Results: Of the 4566 patients who underwent CTO PCI at 25 centers, 196 (4.2%) had coronary artery perforation. Patients with perforations were older (69 ± 10 vs. 65 ± 10, p  < 0.001), more likely to be women (19% vs. 13%, p  = 0.009), more likely to have a history of prior coronary artery bypass graft (34% vs. 20%, p  < 0.001), and unfavorable angiographic characteristics such as blunt stump (62% vs. 48%, p  < 0.001), proximal cap ambiguity (52% vs. 34%, p  < 0.001), and moderate‐severe calcification (60% vs. 49%, p  = 0.002). Technical success was lower in patients with perforations (73% vs. 88%, p  < 0.001). The area under the receiver operating characteristic curve of the PROGRESS‐CTO perforation risk model was 0.76 (95% confidence interval [CI], 0.72−0.79), with good calibration (Hosmer‐Lemeshow p  = 0.97). We found that the CTO PCI perforation risk increased with higher PROGRESS‐CTO perforation scores: 0.3% (score 0), 2.3% (score 1), 3.1% (score 2), 5.5% (score 3), 7.5% (score 4), 14.6% (score 5). Conclusion: Given the good discriminative performance, calibration, and the ease of calculation, the PROGRESS‐CTO perforation score may facilitate assessment of the risk of perforation in patients undergoing CTO PCI.